Anesthetic management of pulmonary endarterectomy in a patient with suprasystemic pulmonary pressure: a case report - Patel, Pravinkumar H.; Panthakey, Harvesp; Katkade, Sandip; Mehta, Hemant (International Journal of Research in Medical Sciences, 2020)
Pulmonary endarterectomy (PEA) is a potentially curative procedure for chronic thromboembolic pulmonary hypertension. A 34-year Indian male presented with supra-systemic pulmonary pressure was taken for PEA after achievable optimization. A successful PEA was performed with the help of total cardiac arrest. Patient developed reperfusion pulmonary edema post operatively, which was managed medically. The problems encountered by anesthesiologists in this case were preoperative pulmonary hypertension with chronic hypoxia and postoperative management of reperfusion pulmonary edema.